High Steroid Sensitivity among Children with Nephrotic Syndrome in Southwestern Nigeria - Taiwo Augustina Ladapo; Christopher Imokhuede Esezobor; Foluso Ebun Lesi (International Journal of Nephrology)
Recent reports from both Caucasian and black populations suggest changes in steroid responsiveness of childhood nephrotic syndrome. This study was therefore undertaken to determine the features and steroid sensitivity pattern of a cohort of black children with nephrotic syndrome. Records of children managed for nephrotic syndrome from January 2008 to April 2013 were reviewed. Details including age, response to treatment, and renal histology were analysed. There were 108 children (median age: 5.9 years, peak: 1-2 years), 90.2% of whom had idiopathic nephrotic syndrome. Steroid sensitivity was 82.8% among children with idiopathic nephrotic syndrome but 75.9% overall. Median time to remission was 7 days. Median age was significantly lower in steroid sensitive compared with resistant patients. The predominant histologic finding in resistant cases was focal segmental glomerulosclerosis (53.3%). No cases of quartan malaria nephropathy or hepatitis B virus nephropathy were diagnosed. Overall mortality was 6.5%. In conclusion, unusually high steroid sensitivity is reported among a cohort of black children. This is likely attributable to the lower age structure of our cohort as well as possible changing epidemiology of some other childhood diseases. Surveillance of the epidemiology of childhood nephrotic syndrome and corresponding modifications in practice are therefore recommended.